Enhanced Electromagnetic Absorption Properties of Commercial Ni/MWCNTs Composites by Adjusting Dielectric Properties - Zhao, Pei-Yan; Wang, Hui-Ya; Wang, Guang-Sheng (Frontiers in Chemistry, 2020)
In this manuscript, we constructed a Ni/MWCNTs absorber and properly adjusted the permittivity resulted from absorber content in the PVDF to optimize impedance matching properties. Both ε′ and ε″ increase obviously with the increasing content of Ni/MWCNTs in PVDF, demonstrating that dielectric properties are dependent on the conductivity. Moderate dielectric properties and excellent impedance matching can be obtained for the filler content of 20 wt% Ni/MWCNTs. Reasonable impedance matching allows electromagnetic waves to propagate into the materials and finally realize energy dissipation through dielectric loss and interfacial polarization. As expected, the minimum reflection loss (RL) of −46.85 dB at 6.56 GHz with a low filler loading (20 wt%) and wide effective bandwidth (RL<-10 dB) of 14.0 GHz in the thickness range of 1.5–5.0 mm was obtained for the commercial Ni/MWCNTs composites, which is promising for mass production in industrial applications. Our findings offer an effective and industrialized way to design high-performance material to facilitate the research in microwave absorption.